APLIKASI PUPUK KOTORAN SAPI DAN PUPUK SP-36 UNTUK MENINGKATKAN HASIL TANAMAN PARE (Momordica charantia L.) - Sepnovit N. Masneno; Shirly S. Oematan; Effy Roefaida (JURNAL AGRISA, 2021)
This research was carried out in the Dry Land of the Faculty of Agriculture, University of Nusa Cendana with the aim to investigate the effect of the application of cow manure and SP-36 fertilizer on the yield of bitter melon. This study was laid out in a randomized block design (RBD) with 6 doses of cow manure and SP-36 fertilizer applications, namely: K0 = without cow manure and SP-36 fertilizer (control), K1 = 10 tons/ha cow manure and SP- 36 fertilizer 50 kg/ha, K2 = 10 tons/ha cow manure and SP-36 fertilizer 100 kg/ha, K3 = 10 tons/ha cow manure and SP-36 fertilizer 150 kg/ha, K4 = 20 tons/ha cow manure and SP-36 fertilizer 50 kg/ha, K5 = 20 tons/ha cow manure and SP-36 fertilizer 100 kg/ha, K6 = 20 tons/ha cow manure and SP-36 fertilizer 150 kg/ha. Each treatment was repeated 3 times in block. The parameters observed were: flowering age, harvesting age, number of fruit/plant, fruit length, fruit weight/plant and fruit weight/plot. The results showed that the application of cow manure and SP-36 fertilizer had a significant effect on all parameters observed. The best treatment in increasing the yield of bitter melon plants was the application of cow manure with dose of 20 tons/ha and SP-36 fertilizer 150 kg/ha. At this treatment, plant had faster flowering and harvesting ages, namely 30 HST and 50 HST, and produced the highest number of fruit/plants (6.8), the longest fruit size (29.90 cm), the heaviest fruit/plant weight (1220.67 gram) and the heaviest fruit/plot weight (18.31 kg).